Analysis of the growing public interest in selective androgen receptor modulators. (12th September 2021) - Efimenko, Iakov V.; Chertman, Willy; Masterson, Thomas A.; Dubin, Justin M.; Ramasamy, Ranjith
Abstract: To characterise trends and interest in selective androgen receptor modulators (SARMs). SARMs are androgen receptor ligands that bind androgen receptors selectively. SARMs have anabolic effects on muscle and bone and were originally synthesised for treatment of muscle wasting conditions, osteoporosis and breast cancer. To date, no SARM has been clinically approved and little is known about their beneficial effects and other adverse effects on users. We examined Google Trend searches of SARMs. Using Google Trends, we analysed how interest in SARMs has evolved over the last 15 years and compared it to trends in testosterone. Comparing 'TRT', 'SARMs' and 'Low Testosterone' together, we see low search interest in SARMs compared to TRT until February 2018, when the interest in both SARMs and TRT terms appear to be the same. Since February 2018, search interest for SARMs has surpassed search interest for both 'TRT' and 'Low Testosterone'. Trends for SARMs demonstrate a continuous increase over the years which has to date surpassed interest for both 'TRT' and 'low testosterone'. The rising interest in SARMs is concerning as the adverse effects of its usage, including its potential effects on fertility, have not been explored. Further investigation is necessary.